THE EFFECT OF BRAND EXPERIENCE AND PERCEIVED QUALITY ON BRAND IMAGE AND BRAND LOYALTY: A STUDY OF IPHONE USERS IN MALANG - Haqqi, Feisal Ikrar (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aimed to determine the effect of brand experience and perceived quality on brand image and brand loyalty from iPhone users. The samples in this research were the users of iPhone in Malang city. The sampling technique was convenience sampling with 150 respondents. This study used Partial Linear Square (PLS) analysis technique to analyse the data. The findings of this study revealed that brand experience has a significant effect on brand image and brand loyalty. Meanwhile, brand image has a significant effect on brand loyalty. Then, perceived quality has a significant effect on brand image, but has no significant effect on brand loyalty. Keywords: Brand Experience, Brand Image, Perceived Quality, and Brand Loyalty